2016
DOI: 10.21451/1984-3143-ar880
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dynamics during oocyte and embryo development and its associationwith environmental induced alterations

Abstract: Epigenetic mechanisms are fundamental to successful gametogenesis and development. The fertilized egg undergoes global DNA demethylation to facilitate remodelling from two differentiated gametespecific states to a pluripotent embryonic state. Maintenance of appropriate levels of DNA methylation during preimplantation development is essential to embryo viability. Recent advances in epigenetic research have highlighted the susceptibility of foetal epigenetic programming to maternal health and nutritional status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(76 reference statements)
0
2
0
1
Order By: Relevance
“…Studies done on mice [ 272 ] and cattle [ 273 ] confirmed maternal diet effects on oocyte DNA methylation. Postpartum cows exposed to negative energy balance and metabolic stress had a number of maternally imprinted genes in their oocytes hypomethylated [ 274 ].…”
Section: In Utero Epigenetics Beyond Art?mentioning
confidence: 99%
“…Studies done on mice [ 272 ] and cattle [ 273 ] confirmed maternal diet effects on oocyte DNA methylation. Postpartum cows exposed to negative energy balance and metabolic stress had a number of maternally imprinted genes in their oocytes hypomethylated [ 274 ].…”
Section: In Utero Epigenetics Beyond Art?mentioning
confidence: 99%
“…However, several studies have shown that gene body methylation is also strongly involved in gene expression [28][29][30], with a bias for exonic regions [31]. Furthermore, epigenetic modifications can be induced by several external factors [32], affecting IVP and MOET embryos differentially. For example, known factors including the in vitro culture medium used [33], and paternal characteristics, such as bull age [34], have been shown to impact at the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%
“…Assim como a BWS, a taxa de desenvolvimento da LOS aumenta significativamente quando os gametas ou embriões são submetidos à alguma técnica de reprodução assistida, seja ovulação da fêmea para coleta de oócitos ou PIVE (CHEN et al, 2013;HAJJ;HAAF, 2013;FAIR, 2016). O estudo desta região gênica utilizando bovinos como modelo animal, principalmente em relação aos genes que sofrem imprinting e demais alterações epigenéticas, podem ajudar a compreender a etiologia das síndromes de imprinting em humanos como a BWS (CHEN et al, 2013).…”
Section: Discussionunclassified